(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Marriage is an important relationships between a men and women. It involves emotional support for each other as well as legal commitment. Education and employment of the Indian women has got significant implications not only for their own lives but for all the lives and relations linked with them. A working woman has to perform two roles. Firstly, a mother and housewife, and secondly of an employee. Both the roles demand on her time and energy. Her employment not only affects her entire personality but also her family relationship and is also liable to face crisis of adjustment which can result in depression. The present study is aimed at exporing the relationship between marital adjustment, stress and depression between working and non working women.